Dampak Pandemi COVID-19 Terhadap Kinerja Keuangan Perusahaan Ritel: Studi Perbandingan Pra dan Pasca Pandemi (Studi Kasus PT Supra Boga Lestari Tbk di BEI Jakarta Tahun 2018-2023) - Ismail Ismail; Afridian (Politeknik Negeri Padang, 2025)
The aim of this The aim of this study is to investigate the impact of the COVID-19 pandemic on the financial performance of PT Supra Boga Lestari Tbk within the 2018-2023 length. The results display a great decline in liquidity ratios, with the present day ratio falling from 1.fifty six times (2018) to zero.seventy eight instances (2023), and the short ratio falling sharply from zero.ninety instances to 0.24 times. The increase in solvency ratios, specifically the DER which rose from 0.79 instances (2018) to 3.17 instances (2023), suggests higher economic risk. Profitability ratios additionally reduced substantially, with ROA falling from 6% (2018) to -10% (2023) and NPM from 2% to -four%. Meanwhile, the Activity ratio showed fluctuations, with TATO and stock turnover lowering in the course of the pandemic, but beginning to reveal recuperation in 2023. In conclusion, the COVID-19 pandemic had a prime impact on the Company financial performance, with a decline in liquidity, solvency and profitability, despite the fact that there have been signs and symptoms of restoration in 2023